Effect of Apical Size and Taper on the Efficacy of Root Canal Disinfection With LED Photodynamic Therapy as an Adjunct to Irrigation With Sodium Hypochlorite: LED-Mediated Photodynamic Therapy in Root Canal Disinfection - Alimadadi, Hoda; Asnaashari, Mohammad; Naseri, Mandana; Yadegari, Zahra (Journal of Lasers in Medical Sciences, 2021)
Introduction: This study assessed the effect of apical size and taper on the efficacy of root canal disinfection with LED photodynamic therapy (PDT) as an adjunct to irrigation with sodium hypochlorite. Methods: A total of 126 extracted human mandibular molars were divided into 4 groups. The mesiobuccal canal was prepared to size 25/4% in group 1, 25/6% in group 2, 30/4% in group 3, and 30/6% in group 4 using the iRaCe rotary system. A 21-day Enterococcus faecalis biofilm was prepared and used for inoculation of the canals. Each group was randomly divided into 3 subgroups for canal disinfection with 2.5% sodium hypochlorite, sodium hypochlorite plus LED PDT, and saline (positive control). Samples from the root canals were obtained with rotary files and cultured. Microbiologic data were analyzed using the Poisson regression test. Results: The bacterial count significantly decreased following disinfection with sodium hypochlorite with/without PDT in all sizes and tapers of preparation compared with the control group (P<0.05). Increasing the apical taper or apical size and the use of PDT as an adjunct did not have a significant effect on the reduction of the bacterial count (P>0.05). However, the apical size and PDT had a significant effect on the number of residual bacteria (P<0.05) and increasing the apical size and conduction of PDT significantly decreased the number of residual bacteria. Conclusion: The apical size and taper and the use of PDT as an adjunct did not have a significant effect on the reduction of the bacterial count. However, increasing the apical size and conduction of PDT as an adjunct to sodium hypochlorite irrigation significantly decreased the number of residual bacteria in the root canal system. DOI: 10.34172/jlms.2021.58